3D model reconstruction with common hand-held cameras. Issue 4 (November 2016) - Zheng, Maoteng; Zhu, Junfeng; Xiong, Xiaodong; Zhou, Shunping; Zhang, Yongjun
Abstract A 3D model reconstruction workflow with hand-held cameras is developed. The exterior and interior orientation models combined with the state-of-the-art structure from motion and multi-view stereo techniques are applied to extract dense point cloud and reconstruct 3D model from digital images. An overview of the presented 3D model reconstruction methods is given. The whole procedure including tie point extraction, relative orientation, bundle block adjustment, dense point production and 3D model reconstruction is all reviewed in brief. Among them, we focus on bundle block adjustment procedure; the mathematical and technical details of bundle block adjustment are introduced and discussed. Finally, four scenes of images collected by hand-held cameras are tested in this paper. The preliminary results have shown that sub-pixel (<1 pixel) accuracy can be achieved with the proposed exterior–interior orientation models and satisfactory 3D models can be reconstructed using images collected by hand-held cameras. This work can be applied in indoor navigation, crime scene reconstruction, heritage reservation and other applications in geosciences.